2010
DOI: 10.1097/mnm.0b013e328330dd14
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of radiolabelled blood cells to lymphatic vessels by intradermal injection: a means of investigating lymphovenous communications in the upper limb

Abstract: Intradermally injected erythrocytes are able to detect and potentially quantify peripheral LVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Labelled erythrocytes administered intradermally were recovered bilaterally from peripheral venous blood (demonstrating the presence of LVCs) in the only patient in the group who did not go on to develop BCRL. 1 As this study assessed only small numbers of patients post-operatively, it was difficult to know whether the LVCs existed prior to surgery, or simply opened-up as a result of surgical intervention to the axilla. The current study aims to further investigate the presence or absence of LVCs in breast cancer patients and to see if these could act as a rescue mechanism in patients who do not develop BCRL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelled erythrocytes administered intradermally were recovered bilaterally from peripheral venous blood (demonstrating the presence of LVCs) in the only patient in the group who did not go on to develop BCRL. 1 As this study assessed only small numbers of patients post-operatively, it was difficult to know whether the LVCs existed prior to surgery, or simply opened-up as a result of surgical intervention to the axilla. The current study aims to further investigate the presence or absence of LVCs in breast cancer patients and to see if these could act as a rescue mechanism in patients who do not develop BCRL.…”
Section: Introductionmentioning
confidence: 99%
“…1 No activity left the injection depot following subcutaneous injection. Following intradermal injection, however, scintigraphy revealed abundant axillary activity, indicating erythrocyte transport up arm lymphatics.…”
Section: Introductionmentioning
confidence: 99%
“…When lymphatic function is impaired, LVCs may open to protect against oedema [5,9]. One such site for LVC may be the skin in patients with 'dermal backflow', but no significant differences were recorded between patients with abnormal lymphoscintigraphic results who had dermal backflow and those who did not.…”
Section: Lymphovenous Communication Stamp and Peters 705mentioning
confidence: 99%
“…For nanocolloid and only 10 nodes, this fraction would be vanishingly small. An obvious explanation is the presence of peripheral lymphovenous communications (LVCs), and there have been several studies claiming to have identified such communications, both physiologically and in patients with lymphoedema [2][3][4][5][6][7][8][9]. An alternative explanation would be the direct transfer of lymph constituents to blood within lymph nodes themselves, and there is also evidence that this takes place [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies claim to have identified anatomic lymphovenous communications, both physiologically and in patients with lymphedema. [1][2][3][4][5][6][7][8][9] There is also evidence to suggest that constituents within lymph may be transferred to blood within lymph nodes.…”
mentioning
confidence: 99%